Perfusion Computed Tomography Scan Imaging in Differentiation of Benign from Malignant Parotid Lesions - Niazi, Masume; Mohammadzadeh, Maryam; Aghazadeh, Kayvan; Sharifian, Hashem; Karimi, Ebrahim; Shakiba, Madjid; Baniasadi, Maria; Rahmaty, Benyamin; Adel, Suzan; Moharreri, Melorina (International Archives of Otorhinolaryngology, 2020)
Introduction The most common site of salivary gland tumors is the parotid gland. Computed tomography (CT), magnetic resonance imaging (MRI), and sonography are imaging modalities to differentiate benign from malignant parotid tumors.Objective The aim of this study is the evaluation of the diagnostic value of perfusion CT for differentiating histological categorization of benign and malignant parotid tumors.Methods A total of 29 patients with parotid neoplasms were enrolled in this study. Mean age and all CT perfusion variables (gradient and permeability, blood flow [BF], blood volume [BV], mean transit time [MTT], permeability surface [PS], maximum intensity projection [MIP], time-density curve [TDC], and time to peak [TTP]) were compared among three groups (malignant tumors [MTs], Warthin's tumor [WT] and pleomorphic adenomas [PA]).Results The mean age of the patients was 55.9 ± 14.1 (26–77), and 15 of them were male (51.7%). Eleven lesions were PAs [37.9%], 8 lesions were WTs (27.6%0 and 10 lesions (34.5%) were MTs (6 acinic cell carcinomas [ACCs], 3 adenocystic carcinomas [AdCCs], and 1 mucoepidermoid carcinoma [MEC]). The mean age of the patients with WTs was 62 ± 7.5 years; 52 ± 14.2 for patients with Pas, and 55.2 ± 17.2 for those with MTs (p = 0.32). The mean MIP was 122.7 ± 12.2 in WT, while it was 80.5 ± 19.5 in PA, and 76.2 ± 27.1 in MTs (p < 0.001); The mean MIP for WT was higher than for PAs and MTs; the values of MTs and PAs were not statistically different. The average of BF, BV, and curve peak were higher in WTs in comparison with the other two groups, and curve time 2 and TTP were higher in PAs in comparison with MTs.Conclusion Based on this study, perfusion CT of the parotid gland and its parameters can distinguish between benign and malignant parotid masses.
Keywords: computed tomography; magnetic resonance imaging; parotid neoplasms; Warthin's tumor; pleomorphic adenoma